Morphology and Conductivity Evaluation of Electrospun Polyacrylic Acid (PAA) Microfiber. (2019) - Ismail, I.; Bakar, N. F.A.; Ling, T.H.; Ideris, N.; Zain, Z. H.M.; Radacsi, N.
Abstract: Electrospinning of polyacrylic acid (PAA) was used to investigate electrical properties and morphology of the fabricated electrospun microfibers as the function of solute concentration. The mean diameter of the fibers increased from 301 to 682 nm with increasing PAA concentrations from 4 to 7 wt %, respectively due to increasing of polymer solution viscosity. At 3 wt % of PAA concentration, the average fiber diameter was higher than 4.0 and 5.0 wt% PAA because the fiber sizes were not homogenous as spindle and junctions were formed. The porosity of 6 wt % electrospun PAA was the highest i.e. 5.89% with the contact angle of 61° which indicated its capability to retain high water or moisture on the surface. The conductivity of the dried electrospun PAA microfiber increased from 1.01×10 -6 to 2.63×10 -5 S/m with increasing of PAA concentrations from 3 to 6 wt% respectively because larger fiber diameter provided more porous structure to retain moisture.